2002
DOI: 10.1080/00306525.2002.11446743
|View full text |Cite
|
Sign up to set email alerts
|

Nectar passage and gut morphology in the Malachite Sunbird and the Black-capped Lory: implications for feeding in nectarivores

Abstract: Mbatha, K., Downs, C.T: & Penning, M. Nectar passage and gut morphology in the Malachite Sunbird and the Black-capped Lory: implications for feeding in nectarivores.Nectar passage and digestive tract morphology of two unrelated nectarivorous bird species, the Malachite Sunbird, Nectarinia famosa, ·and the Block-capped Lory, Lorjus·/or~were examined. X-ray techniques were. used to determine the gross anatomy, and the flow of nectar (an artificial sugar solution) along the gastrointestinal tract. The Black-cappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In contrast, birds that feed less frequently or at long, irregular intervals would have considerable more variation in their plasma glucose concentrations, depending on their feeding rate and the size of their meal (Work 1996;Beuchat and Chong 1998). However, Malachite Sunbirds have no crop for nectar storage (Mbatha and Downs 2002;Downs 2004) and so these birds need to feed frequently during the day to maintain their plasma glucose concentrations and to meet their energy requirements (Downs 2000). Most diurnal birds, like Malachite Sunbirds, feed only during the photophase and then fast during the scotophase.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, birds that feed less frequently or at long, irregular intervals would have considerable more variation in their plasma glucose concentrations, depending on their feeding rate and the size of their meal (Work 1996;Beuchat and Chong 1998). However, Malachite Sunbirds have no crop for nectar storage (Mbatha and Downs 2002;Downs 2004) and so these birds need to feed frequently during the day to maintain their plasma glucose concentrations and to meet their energy requirements (Downs 2000). Most diurnal birds, like Malachite Sunbirds, feed only during the photophase and then fast during the scotophase.…”
Section: Discussionmentioning
confidence: 91%
“…Unlike hummingbirds, sunbirds have no crop or distensible oesophagus for storage (Mbatha, Downs & Penning 2002). Under most conditions, hummingbirds fill their crops to only 10–30% of capacity, but crops enable them to maximize nectar intake during opportunistic feeding by individuals without territories (Carpenter et al .…”
Section: Discussionmentioning
confidence: 99%
“…Small birds show no significant difference in overall energy intake between diets of different sugar concentrations (Lloyd 1991;Downs 1997a;Lopez-Calleja & Bozinovic 2003;Markman et al 2006). This may also be a function of gastrointestinal structure, as it has been shown that several small nectarivores lack a crop, and so do not have a storage capacity for ingesta (Mbatha & Downs 2002). By contrast, nectarivorous species with larger crop storing capacities show a less marked sugar preference with change in concentration (Downs 1997b).…”
Section: Introductionmentioning
confidence: 89%